TRADISI PEGI TEPAT MASYARAKAT DESA TALANG PETAI KABUPATEN MUKOMUKO DALAM PERSPEKTIF HUKUM ISLAM - Jamal Mirdad; Al Ikhlas (JURIS (Jurnal Ilmiah Syariah), 2018)
Pilgrimage tradition in Indonesia is a phenomenon that has not been eradicated by the times. The more modern and sophisticated technology, the more pilgrims come. In each city and region there are many people who cult certain graves to the point that the tomb can solve their problems. The tradition of the grave pilgrimage or the term in Mukomuko Regency is "pegi tepat."  It is a traditional practice carried out every year. Many practices that come from outside the teachings of Islam even there are deviations from the teachings of Islam itself such as: prostration on the grave, asking for healing, enliven the grave and combining between tradition and religion.